New echinocandin susceptibility patterns for nosocomial Candida albicans in Bogotá, Colombia, in ten tertiary care centres: An observational study (2015)
Background: Candida albicans remains as the first cause of nosocomial fungal infections in hospitals worldwide and its susceptibility pattern should be better described in our tertiary care hospitals. Methods: This study aimed at identifying the caspofungin susceptibility pattern regarding nosocomial Candida albicans infection in ten tertiary care hospitals using the methodology proposed by CLSI M27-A3 and CLSI M27-S4, and its association with risk factors and clinical outcome. The approach involved descriptive research concerning the diagnosis of nosocomial infection during a 7-month period in 10 hospitals in Bogotá, Colombia. Associations were established using exact non-parametric statistical tests having a high statistical power (>95%), suitable for small samples. The exact Mann Whitney test or Kruskall-Wallis non-parametric ANOVA tests were used for distributions which were different to normal or ordinal variables when comparing three or more groups. Multivariate analysis involved using binomial, multinomial and ordinal exact logistical regression models (hierarchical) and discrimination power was evaluated using area under the ROC curve. Results: 101 nosocomial infections were found in 82,967 discharges, for a Candida spp. infection rate of 12.2 per 10,000 discharges, 30.7% caused by C. albicans, 22.8% by C. tropicalis, 20.8% by C. parapsilosis, 19.8% by other Candida, 3% by C. krusei and 3% by C. glabrata. Statistically significant associations between mortality rate and the absence of parenteral nutrition were found in multivariate analysis (OR = 39.746: 1.794-880.593 95% CI: p = 0.020). The model's predictive power was 83.9%, having an 85.9% significant prediction area (69.5%-100 95% CI; p = 0.001). Conclusions: Significant differences were found regarding susceptibility results when comparing CLSI M27-A3 to CLSI M27-S4 when shifting clinical break-point values. However, one nosocomial strain was consistent in having reduced susceptibility when using both guidelines without having been directly exposed to echinocandins beforehand and no mutations were found in the FKS1 gene for hot spot 1 and/or hot spot 2 regions, thereby highlighting selective pressure regarding widespread antifungal use in tertiary healthcare centres. Nutritional conditions and low family income were seen to have a negative effect on survival rates. © 2015 Rodríguez-Leguizamón et al.; licensee BioMed Central.